Exploring the Functional and Spiritual Dimensions of the Pre-Ramadan Tradition Smiyauh Nunggau within the Living Qur’an Framework - Mohd Detrial Maulana; Ican Mandala; Ahmad Rial Al-Fajri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Prayer is a fundamental act of worship in Islam. Beyond obligatory prayers, the Prophet Muhammad (PBUH) also encouraged various forms of non-obligatory prayers, one of which is the tradition of Smiyauh Nunggau, or congregational prayer for forty consecutive days before Ramadan, as practiced in Koto Padang Village, Tanah Kampung Subdistrict, Sungai Penuh City, Jambi Province, Indonesia. This tradition is predominantly upheld by women, who gather to perform the five daily prayers in congregation at the mosque or musalla. Conducted annually from the end of Jumadil Akhir to the end of Rajab, this practice has become integral to the community’s religious life. This study examines three key aspects: (1) the transmission of the forty-day prayer tradition in Koto Padang Village, (2) its relevance to the concept of the Living Qur’an, and (3) its functional and spiritual values. Using a qualitative field research methodology grounded in the Living Qur’an framework and participatory observation, data were collected through interviews, observations, and active participation. The findings reveal that Smiyauh Nunggau has been practiced since before the 1990s and aligns with the teachings of the Syattariyah order, rooted in the Prophet’s hadith. Functionally, the tradition fosters social cohesion and reminds the community of the upcoming Ramadan. Spiritually, it instills consistency (istiqamah) and strengthens faith. This study highlights the tradition’s role in promoting social bonds and spiritual discipline while contributing to broader discussions about the Living Qur’an in the context of Indonesian Islamic traditions.